Structural Versatility of Bicellar Systems and Their Possibilities as Colloidal Carriers - López Olga; López-Iglesias Carmen; De la Maza Alfons; Rubio Laia; Cócera Merce; Rodríguez Gelen; Barbosa-Barros Lucyanna (MDPI AG, 2011)
Bicellar systems are lipid nanostructures formed by long- and short-chained phospholipids dispersed in aqueous solution. The morphological transitions of bicellar aggregates due to temperature, composition and time variations have been revised in this work. To this end, two bicellar systems have been considered; one formed by dimyristoyl-phosphatidylcholine (DMPC) and dihexanoyl- phosphatidylcholine (DHPC) and another formed by dipalmitoyl-phosphatidylcholine (DPPC) and DHPC. The relationship between the magnetic alignment, the morphology of the aggregates and the phase transition temperature (Tm) of lipids is discussed. In general terms, the non-alignable samples present rounded objects at temperature below the Tm. Above this temperature, an increase of viscosity is followed by the formation of large elongated aggregates. Alignable samples presented discoidal objects below the Tm. The best alignment was achieved above this temperature with large areas of lamellar stacked bilayers and some multilamellar vesicles. The effect of the inclusion of ceramides with different chain lengths in the structure of bicelles is also revised in the present article. A number of physical techniques show that the bicellar structures are affected by both the concentration and the type of ceramide. Systems are able to incorporate 10% mol of ceramides that probably are organized forming domains. The addition of 20% mol of ceramides promotes destabilization of bicelles, promoting the formation of mixed systems that include large structures. Bicellar systems have demonstrated to be morphologically stable with time, able to encapsulate different actives and to induce specific effects on the skin. These facts make bicellar systems good candidates as colloidal carriers for dermal delivery. However, water dilution induces structural changes and formation of vesicular structures in the systems; stabilization strategies have been been explored in recent works and are also updated here.